Effects of aerobics training on anxiety, depression and sleep quality in perimenopausal women - Zhao, Yan; Niu, Hualiang; Liu, Shengjie (Frontiers in Psychiatry, 2022)
ABSTRACT: Objective: To investigate the effect of aerobics training on anxiety, depression and sleep disturbance in perimenopausal women. Methods: 121 perimenopausal women with anxiety, depression or sleep disorder in Lishi district of Luliang city were treated with aerobics training. Self-rating anxiety scale, self-rating depression scale and Pittsburgh sleep scale were used to investigate the anxiety, depression and sleep status of perimenopausal women before and after intervention. Results: After aerobics training, the scores of self-rating anxiety scale, self-rating depression scale and Pittsburgh sleep questionnaire were 48.26 ± 6.47, 50.27 ± 6.54 and 10.64 ± 4.38, respectively. The levels of anxiety, depression and sleep disorder in 121 subjects were significantly lower than those before intervention (t = 3.865, 4.541, 5.596, P < 0.01). The remission rate of symptoms was significantly different in subjects with different frequency of spontaneous practice (P < 0.01), and the higher the number of spontaneous practice, the higher the remission rate of anxiety, depression and sleep disorders in subjects (P < 0.01). Conclusion: aerobics training can effectively improve the anxiety and depression of perimenopausal women, improve sleep quality, the more frequency of practice, the more obvious the effect. It can be used as an intervention to improve the mental health level of perimenopausal women in terms of anxiety, depression and sleep quality in clinical promotion.